Socio-Economic Factors of Consumer Choice of Private Sector Health Care Services - Žemgulienė, Jolanta (Ekonomika, 2001)
Most inputs for the health sector can be more efficiently produced and quality of the service can be improved by exposing public services to competitive market forces, reducing the size of the public sector and increasing private sector participation. Rebalancing the complex mix of public and private roles in the health sector it is important to evaluate factors of influence on the consumers choice of private health care providers. In this article we assessed the differences in use of private health care services among different socio-economic groups over the period 1997-1998. The multivariate logistic regression was used for the analysis of the Lithuanian household survey data. The study the factors of consumer choice the regression coefficients were calculated for the various socio-economic, health status measures. Analysis showed that younger people with higher education and higher income living in bigger towns reporting poor health, use the private health care services more frequently. Income is the factor influencing the access to private health care. During the analysed period 28 percent of inhabitants preferred to use private health care providers’ services.